POD07 Tinnitus and hyperacusis in semantic dementia. Issue 11 (22nd October 2010) - Mahoney, C; Rossor, M N; Rohrer, J D; Warren, J D; Fox, N C; Goll, J C
Abstract : Introduction: Semantic dementia (SemD) is a canonical subtype of frontotemporal lobar degeneration characterised by progressive fluent aphasia in the context of focal asymmetric (predominantly left-sided) anterior temporal atrophy. Nonverbal auditory symptoms (particularly heightened sensitivity to sound) are often reported in SemD but remain poorly understood. Methods: We retrospectively reviewed the clinical records of a consecutive series of 43 SemD cases at a specialist cognitive clinic over a 15 year period and recorded whether patients had ever complained of tinnitus or hyperacusis. In historical cases relatives were approached to confirm the clinical history and where possible patients' peripheral hearing was assessed. All patients underwent volumetric brain MRI and voxel-based morphometry was used to assess grey matter profiles in SemD cases with and without auditory symptoms. Results: Eight (19%) patients reported tinnitus, six (14%) reported hyperacusis, while 29 (67%) reported no auditory symptoms. Compared with cases without auditory symptoms, SemD cases with tinnitus or hyperacusis had increased grey matter in the posterior superior temporal gyrus and reduced grey matter in more anterior cortical regions. Conclusion: Abnormal auditory percepts appear to be relatively common in SemD and may arise from altered coupling between damaged anterior temporal and less affected posterior auditory cortical areas.